THE VENDIAN (EDIACARAN) IN THE GEOLOGICAL RECORD: ENIGMAS IN GEOLOGY'S PRELUDE TO THE CAMBRIAN EXPLOSION - McCall G.J.H. (My University, 2006)
Up to the 1950s, the Precambrian was regarded as unrewardingly unfossiliferous, records of fossils being isolated, few in number and dubious. The change came with the discovery by Reg Sprigg of body fossils in latest Proterozoic sediments in South Australia. Although there had been descriptions of isolated fossils (now recognised as Ediacaran) from rocks of this age in the nineteenth century and at the start of the twentieth century, in Newfoundland and Namibia, respectively, the Ediacara finds stimulated researches and now, at the start of the twenty-first century, diversified fossil assemblages are known, all over the world, from the period 600-543 Ma, known formerly as the Vendian and now officially as the Ediacaran. In this account, a brief description of the history of these finds is given, followed by descriptions of the most important provinces [South Australia, Leicestershire, Namibia, Russia (Podolia, the White Sea Coast, Urals and Siberia), Newfoundland (Avalon Peninsula) and Northwest Canada]: then of 27 other known occurrences of this dominantly soft-bodied and perplexing fauna(?)-it seems certain that some, at least of the fossils, are animal fossils, although some, even the greater part, could be a unique form of life, not animals or plants ("Vendobionta"). These descriptions, derived in the course of a literature search lasting over a year, are followed by discussions of important special aspects: trace fossils; geochronology and correlation; geotectonics; glaciation (the "Snowball Earth" concept applied to the Varangian/Laplandian/Marinoan glaciation, which ushered in this last subdivision of the Proterozoic); the evidence for Ediacaran and other life forms existing in the Proterozoic prior to its last, Ediacaran, chronological subdivison; the Vendozoa concept. The last section consists of short summary of conclusions. This text essentially constitutes an objective record of what has been published to 2005 on the Ediacaran System. © 2006 Elsevier B.V. All rights reserved.
Keywords: BODY FOSSILS (SOFT-BODIED); EDIACARAN; GLACIATION; NEOPROTEROZOIC; TRACE FOSSILS; VENDIAN; Докембрий::Протерозой::Неопротерозойская::Эдиакарий; Precambrian::Proterozoic::Neoproterozoic::Ediacaran